Sudan : World Bank Review of 2008 Budget Performance and 2009 Budget Preliminary Analysis - World Bank (Washington, DC, 2013)
As a follow-up to the first Public Expenditure Review (PER), this note reviews fiscal management by the Government of National Unity (GoNU) through 2008 budget performance, including pro-poor spending, and how do its main features compare to the fiscal management under the first phase of the post-CPA interim period (2005-07)? The note also runs through the highlights of the key features of the GoNU 2009 budget and what has been the impact of the global crisis on the budget performance through the first quarter. The main objective is to highlight fiscal lessons for the remaining period of the post-CPA interim period. The note is structured around the following six sections: review of the economic assumptions underlying the 2008 budgets, aggregate fiscal performance, revenue performance, expenditure performance, pro-poor spending, and the 2009 budget analysis followed by actual outturns through the first quarter.